Community based participatory research for improved mental healthcare a manual for clinicians and researchers - Roberts, Laura Weiss (Springer New York, 2013)
Respect for persons, beneficence, and justice are the principles that collectively form the ethical basis of human research. These three principles find expression in Community-based participatory research for improved mental Healthcare, or CBPR – a systematic approach for engaging specially-defined groups of people in a process of inquiry and social change. In Community-based participatory research, a panel of renowned authors provide a step-by-step approach for conducting CBPR, providing all the conceptual and methodological guidelines needed to implement this important and extremely fruitful research approach. As early career investigators use this mode of collaborative inquiry in the service of society, an exciting and entirely new capacity for ethically sound and more rigorous and consequential science can be built. An indispensable resource that will be of great interest to researchers from a wide array of disciplines, Community-based participatory research for improved mental healthcare is a major addition to the literature and certain to become the gold standard reference in the field. What is community-based participatory research? -- Background preparation for the CBPR process -- Beginning partnerships with communities -- Finding common ground within the partnership -- Sustaining the partnership -- Evaluating the partnership and enhancing future successes -- Appendix A Researcher guide -- Appendix B Community brochure (sample pages) -- Appendix C Facilitator guide -- Appendix D Meeting poster (sample) -- Appendix E Newspaper recruitment ad (sample) -- Appendix F glossary -- References -- Recommended reading -- Index